2015
DOI: 10.1016/j.humov.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Advanced age brings a greater reliance on visual feedback to maintain balance during walking

Abstract: We implemented a virtual reality system to quantify differences in the use of visual feedback to maintain balance during walking between healthy young (n = 12, mean age: 24 years) and healthy old (n = 11, 71 years) adults. Subjects walked on a treadmill while watching a speed-matched, virtual hallway with and without mediolateral visual perturbations. A motion capture system tracked center of mass (CoM) motion and foot kinematics. Spectral analysis, detrended fluctuation analysis, and local divergence exponent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
103
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 36 publications
7
103
0
1
Order By: Relevance
“…Incorrect step placement can then further compromise mediolateral balance, requiring subsequent recovery steps to restore balance, thereby contributing to the increase in step width variability observed here. Interestingly, we previously found that the visual perturbation frequencies permeate old adult's center of mass motion [28]. That old adults' gait patterns entrain to one or both of the frequencies used in the perturbed visual flow further supports the idea that they were relying upon the aberrant visual feedback in their sensorimotor control of walking.…”
Section: Discussionmentioning
confidence: 75%
“…Incorrect step placement can then further compromise mediolateral balance, requiring subsequent recovery steps to restore balance, thereby contributing to the increase in step width variability observed here. Interestingly, we previously found that the visual perturbation frequencies permeate old adult's center of mass motion [28]. That old adults' gait patterns entrain to one or both of the frequencies used in the perturbed visual flow further supports the idea that they were relying upon the aberrant visual feedback in their sensorimotor control of walking.…”
Section: Discussionmentioning
confidence: 75%
“…2 Sensory reweighting provides a compensatory mechanism for altered afferent input arising from musculoskeletal injuries and aging. [3][4][5][6] Specifically, a recent meta-analysis 3 found that patients with chronic ankle instability re-weight to visual feedback to maintain single-limb balance, as a compensatory mechanism for reduced fidelity of somatosensory input from the injured ankle joint.…”
mentioning
confidence: 99%
“…5,6 This visual reliance may enable patients with somatosensory deficits to maintain standing balance, but it can be dangerous during activities of daily living or/and sports. These activities often involve multiple tasks; thus, patients' visual attention may be largely diverted from balance control, revealing the deficiencies in the compensatory mechanism and possibly resulting in falls and/or injury.…”
mentioning
confidence: 99%
“…Prior studies have shown that older adults rely more on visual feedback to maintain balance during walking than younger adults, and those with significant visual impairment have slower walking speeds compared to age-matched controls. 2021 Moreover, one study found that proprioceptive feedback exercises improved walking speed in individuals with Parkinson’s disease, suggesting the importance of proprioceptive inputs to gait function. 22 We adjusted for both visual acuity and monofilament testing in our regression models and did not observe that these factors explained the association between static balance and walking speed.…”
Section: Discussionmentioning
confidence: 99%